PENGUJIAN KANDUNGAN UNSUR HARA DALAM KOMPOS YANG BERASAL DARI SERASAH TANAMAN JAGUNG MANIS (Zea mays saccharata) - SURTINAH SURTINAH (Universitas Lancang Kuning, 2013)
ABSTRACTThis study aims to determine the nutrient content of the compost derived from sweet corn crop residues after harvest. This research is descriptive, wherein the first process is the process of making compost derived from corn crop residue after harvest, are composted for 1 month by using bio activator EM-4. To measure the content of macro nutrients, the test method used is the Kjeldahl method for nitrogen content, while for P, K, CaO, MgO and Fe Atomic absortion spectrophotometric used method (AAS), and the content of C - Organic tested by Spectrophotometric method.Laboratory test results on the compost derived from sweet corn litter containing N 1:05%, 1.01% P2O5, 0.18% K2O, CaO 1.98%, MgO 0.53%, C - 10.5% Organic, and C / N ratio of 9.97.